Optimalisasi Manajemen Rantai Pasok PT. Mond Nature Lestari dalam Pengolahan Produk Daun Kelor Berbasis Permintaan Pasar - Lailatul Syifa Tanjung; Yesi Yusmita; Hidayati Rusnedy; Kasini (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2025)
This community service program aims to optimize supply chain management at PT. Mond Nature Lestari, an MSME processing products made from moringa leaves. The main problems faced by partners are irregular raw material supplies, manual stock recording, and production that is not yet based on market demand. The solutions offered include digital recording training using Google Sheet, raw material procurement planning, and designing production and distribution systems based on demand data. The results of the activities showed an increase in operational efficiency, stock accuracy, and distribution timeliness. This optimization is expected to increase business competitiveness and become a model for similar MSMEs.